Obesity – threat to the reproductive potential of Russia - Elena N. Andreeva (Ожирение и метаболизм, 2019)
Obesity is a recurring polyetiological disease. Overweight are 30–60% of women of reproductive age, and 25–27% are obese. By 2025, it is expected that 50% of women on our planet will be obese. Obesity in women of reproductive age is accompanied by a high frequency of anovulation, hyperandrogenism, menstrual irregularities, endometrial pathology, infertility. During pregnancy, this group of women has a higher risk of short term loss, including pregnancy in the outcome of assisted reproductive technologies. Weight gain and obesity can lead to decreased fertility in women. The body mass index of a woman of reproductive age negatively affects the course of pregnancy, namely: the risk of gestational diabetes, increased blood pressure, eclampsia, the pathological course of the birth act and the pathology of the newborn increase. Obesity in women of reproductive age is an independent risk factor for cancer: breast cancer and endometrial cancer, and also leads to a decrease in the survival rate for ovarian cancer. Obesity often accompanies polycystic ovary syndrome, which occurs in every 10th patient of reproductive age. The combination of these diseases increases the risk of cardiometabolic conditions such as impaired glucose tolerance, type 2 diabetes and dyslipidemia. Weight loss in these patients is a necessary component of complex therapy aimed at improving reproductive potential.